Semantic loss marks early Alzheimer's disease‐related neurodegeneration in older adults without dementia. Issue 1 (5th August 2020) - Vonk, Jet M. J.; Bouteloup, Vincent; Mangin, Jean‐François; Dubois, Bruno; Blanc, Frédéric; Gabelle, Audrey; Ceccaldi, Mathieu; Annweiler, Cédric; Krolak‐Salmon, Pierre; Belin, Catherine; Rivasseau‐Jonveaux, Thérèse; Julian, Adrien; et al.
Abstract: Objective: To assess progression of semantic loss in early stages of cognitive decline using semantic and letter fluency performance, and its relation with Alzheimer's disease (AD)‐specific neurodegeneration using longitudinal multimodal neuroimaging measures. Methods: Change in verbal fluency was analyzed among 2261 non‐demented individuals with a follow‐up diagnosis of no mild cognitive impairment (MCI), amnestic MCI (aMCI), non‐amnestic MCI (naMCI), or incident dementia, using linear mixed models across 4 years of follow‐up, and relations with magnetic resonance imaging (MRI; n = 1536) and 18 F‐fluorodeoxyglucose brain positron emission tomography ( 18 F‐FDG‐PET) imaging (n = 756) using linear regression models across 2 years of follow‐up. Results: Semantic fluency declined—fastest in those at higher risk for AD (apolipoprotein E [APOE] e4 carriers, Clinical Dementia Rating score of .5, aMCI, or incident dementia)—while letter fluency did not except for those with incident dementia. Lower baseline semantic fluency was associated with an increase in white matter hyperintensities and total mean cortical thinning over time, and regionally with less hippocampal volume as well as more cortical thinning and reduced 18 F‐FDG‐PET uptake in the inferior parietal lobule, entorhinal cortex, isthmus cingulate, and precuneus–posterior cingulate area. In contrast, baseline letter fluency was not associated with change in total nor regional neurodegeneration. Whole‐brain neurodegeneration over time was associated with faster decline in both fluencies, while AD‐specific regions were associated with a faster rate of decline in semantic but not letter fluency. Interpretation: This study provides strong evidence of distinctive degeneration of semantic abilities early on in relation to both cognitive decline and AD‐specific neurodegeneration.